الحوكمة الطبية فى التحسين المستمر للخدمات الصحية : دراسة تطبيقية - زيدان، عبدالعزيز محمد أيوب (جامعة بورسعيد - كلية التجارة, 2014)
يتناول هذا البحث مجال هام من مجالات حوكمة الشركات وهو الحوكمة الطبية ودورها في التحسين المستمر للخدمات الصحية، حيث تطرق هذا البحث إلى التعريف بالحوكمة الطبية، أهداف الحوكمة الطبية، مبادئ الحوكمة الطبية، أهمية تطبيق الحوكمة الطبية، مزايا تطبيق الحوكمة الطبية في القطاع الصحي، كما تم تناول مفهوم وأهداف التحسين المستمر، مفاهيم وعناصر جودة الخدمات الصحية وأهدافها وخصائصها، مفهوم وأهداف ومجالات التحسين المستمر للخدمات الصحية. كما يتناول هذا البحث بناء مدخل محاسبي مقترح لتفعيل دور الحوكمة الطبية في التحسين المستمر للخدمات الصحية تتمثل عناصره في التحسين المستمر لأخلاقيات المهن الطبية، التحسين المستمر للرقابة المالية والطبية، التحسين المستمر لجودة المعلومات المحاسبية، التحسين المستمر لدور لجنة المراجعة، التحسين المستمر لحفظ حقوق أصحاب المصالح، التحسين المستمر للتعليم والتدريب والبحث العلمي للأطقم الطبية، التحسين المستمر لإدارة المخاطر والشكاوى الطبية. وأخيرا يتناول هذا البحث إعداد دراسة تطبيقية على القطاع الصحي لتعظيم الاستفادة من عناصر المدخل المحاسبي المقترح لتفعيل دور الحوكمة الطبية في التحسين المستمر للخدمات الصحية ومن خلال تطبيق آليات الحوكمة الطبية الرشيدة. This research is an important area of corporate governance, a governance Medical and its role in the continuous improvement of health services, which touched on this research to introduce the governance of medical, goals governance of medical, corporate governance principles, medical importance of the application of governance, medical advantages of the application of the governance of medical in the health sector, as was the concept of continuous improvement and the goals, concepts and elements of quality health services, objectives and characteristics, the concept, objectives and areas of continuous improvement of health services. It also addresses this research building proposed accounting approach to activate the role of governance medical in the continuous improvement of health services are elements in the continuous improvement of the ethics of the medical profession, the continuous improvement of financial control, medical, continuous improvement of the quality of accounting information, the continuous improvement of the role of the audit committee, the continuous improvement of the preservation of the rights of stakeholders , the continuous improvement of education, training and scientific research for medical kits, continuous improvement of risk management and medical complaints. Finally, This research deals with the preparation of an applied study on the health sector to maximize the benefit of the elements of the proposed accounting entrance to activate the role of medical governance in the continuous improvement of health services and through the application of medical good governance mechanisms.
Keywords: الحوكمة الطبية -- الخصخصة -- الخدمات الصحية -- مصر